Prevodno leposlovje v sodobni Sloveniji - Blatnik, Andrej (Knjižnica, 2017)
Based on a typological model from sociology, this article analyzes literary translation support mechanisms in the world and especially in Slovenia. It tracks the growing inclusion of translation policies in the national cultural policies and subsequent growth of the translated books in the book subsidy system and their strong presence in the reading field. With the help of statistical date it shows that in the Slovenian public libraries, translated literature is chosen approximately four times as much as original Slovenian; at the end, the article is reflecting the effect of this fact on the Slovenian reading field.
Keywords: bralno polje; cultural policies; kulturna politika; literarno prevajanje; prevodi; prevodno leposlovje; reading field; Slovene publishing; slovensko založništvo; translating; translation of fiction